2021
DOI: 10.1002/ajs4.158
|View full text |Cite|
|
Sign up to set email alerts
|

How are gender inequality and violence against women related? Findings from a population‐level community attitudes survey

Abstract: Low support for gender equality (GE) predicts attitudes supporting violence against women (VAW). However, little is known about the influence of attitudes toward different manifestations of GE. This study extends knowledge by assessing the relative strength of attitudes to GE across seven theoretically derived dimensions, and their association with attitudes toward VAW. 17,542 Australians participated in the 2017 National Community Attitudes Towards Violence Against Women Survey. Population means were calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
76
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(78 citation statements)
references
References 57 publications
1
76
1
Order By: Relevance
“…Workplaces have been identified as social spaces where change that addresses and seeks to eliminate sexual violence perpetrated against women can be implemented and enforced through gender equity measures [ 36 ]. Yet this form of violence remains rife and poorly addressed, despite legal interventions that have made sexual violence a criminal offense, and the widespread implementation of diversity management and training [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Workplaces have been identified as social spaces where change that addresses and seeks to eliminate sexual violence perpetrated against women can be implemented and enforced through gender equity measures [ 36 ]. Yet this form of violence remains rife and poorly addressed, despite legal interventions that have made sexual violence a criminal offense, and the widespread implementation of diversity management and training [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is also an economic burden associated with men's violence against women, which includes dating violence, and conservative estimates show that gendered IPV cost the Australian economy about $22 billion for the year -16 (KPMG Australia, 2016. Despite the social and health impacts of dating violence, Australian research has shown that public attitudes supportive of gendered violence against young women are rife (Hall and Partners Open Mind, 2015;Politoff et al, 2019;Webster et al, 2018), but there is little research exploring the issue from the perspective of the young women who experience this injustice.…”
Section: Rationalementioning
confidence: 99%
“…Dating violence is a prevalent and important public health concern with numerous health and social impacts. However despite these burdens, there is varied understanding and awareness of dating violence by young women and the general public in Australia (Hall and Partners Open Mind, 2015;Politoff et al, 2019;Webster et al, 2018). An Australian study exploring over three thousand young people's attitudes towards men's violence against women revealed that most participants were unable to articulate what a healthy and respectful relationship encompassed (Hall and Partners Open Mind, 2015).…”
Section: Public Appraisal Of Dating Violencementioning
confidence: 99%
See 1 more Smart Citation
“…The Australian National Community Attitudes towards Violence against Women Surveys (NCAS) found a significant difference between Australians and migrants from non-English-speaking countries regarding attitudes toward violence against women (Taylor & Mouzos, 2006; Webster et al, 2014, 2019). People from non-English-speaking countries were significantly less likely to view stalking or harassment by telephone or email as violence.…”
Section: Introductionmentioning
confidence: 99%